Surgical Complications from Superior Canal Dehiscence Syndrome Repair: Two Decades of Experience. (27th June 2017) - Xie, Yanjun; Sharon, Jeffrey D.; Pross, Seth E.; Abt, Nicholas B.; Varma, Sanskriti; Della Santina, Charley C.; Minor, Lloyd B.; Carey, John P.
Abstract : Objective: To determine the incidence of surgical complications associated with superior canal dehiscence syndrome (SCDS) repair and identify the demographic, medical, and intraoperative risk factors that are associated with SCDS complications. Study Design: Cases series with chart review, including patients who underwent SCDS repair between 1996 and 2015. Setting: A tertiary care academic medical center. Subjects and Methods: Data were collected from 220 patients, including demographic information, medical comorbidities, prior otologic surgical history, surgical approach, intraoperative findings, and postoperative complications. Relative risk analysis and multivariable logistic regression evaluated the associations between perioperative risk factors and SCDS complications. Results: A total of 242 consecutive cases were performed: 95.5% middle fossa and 4.5% transmastoid approach (mean age: 47.8 ± 10.6 years; 54.5% female). Surgical complications were reported in 27 (11.2%) cases; 20 (8.3%) had Clavien‐Dindo grade I complications, most commonly benign paroxysmal positional vertigo (n = 11, 4.5%) and profound sensorineural hearing loss (n = 6, 2.5%). Two cases (0.8%) had grade II; 4 cases (1.7%), grade III; and 1 case (0.4%), grade IV complications. In the analysis of comorbidities, only preoperative coagulopathy was significantly associated with increased risk of complications (relative risk = 6.4, P <. 01). Following multivariate logistic regression adjusting for demographic covariates, coagulopathy was still associated with increased odds of complications (odds ratio = 15.7, P =. 03). There were no significant associations between other risk factors and complications. Conclusion: SCDS repair has low rates of adverse events. We observed an incidence of 11.2% complications, most commonly postoperative benign paroxysmal positional vertigo. The risk of nonotologic intracranial complications (1.7%) is low.